Methodology for the inspection of the tool in the drilling of parts - Herrera-Baquero, Lizeth Paola; Prieto-Ortiz, Flavio Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this paper two methodologies are proposed to minimize the possible errors in the finished parts due to fault in the drilling tool, the first is done before starting the machining, where the initial positions of the tool are verified with respect to the piece, the cutting angle, diameter and length of it. The second is during the machining, through a continuous interaction with the Mach3® software, the cutting angle and the length of the drill are verified, all this to perform a feedback with the user and determine the current state of the tool. In this development, computer vision techniques of low computational cost were used to reduce processing times and obtain a representation of the scene as real as possible. Finally, the proposed methodologies are evaluated in a specific case study where their efficiency is proven.